1993
DOI: 10.1007/bf02236884
|View full text |Cite
|
Sign up to set email alerts
|

Preweaning growth performance of West African shorthorn cattle and their Jersey crossbreds in Ghana

Abstract: Calf records on 621 West African Shorthorn (WASH) and 3 grades of Jersey x WASH crossbreds were analysed for the effects of the level of Jersey breeding and other factors on birth weight, 205-day weaning weight and average daily gain (ADG). Crossbred calves were significantly (P < 0.01) heavier at birth than purebred WASH and birth weights increased with increasing level of Jersey breeding. No significant differences were established for 205-day weaning weight, however ADG declined with increasing level of Jer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Similar, but slightly higher LWGs have been reported for indigenous calves (Pagot, 1992;Ogungbe and Adu, 1998). Furthermore, crossbred yearling cattle have been shown to gain more weight, over a specified period, than their purebred counterparts under similar conditions although, the negative impacts of the tropical environment sometimes affect their performance negatively (Ahunu et al, 1993). The overall LWG recorded for the calves in the trials were lower than the range from 295 to 525 g d − 1 average daily gains reported for preweaned calves by Messine et al (2004).…”
Section: Discussionmentioning
confidence: 48%
“…Similar, but slightly higher LWGs have been reported for indigenous calves (Pagot, 1992;Ogungbe and Adu, 1998). Furthermore, crossbred yearling cattle have been shown to gain more weight, over a specified period, than their purebred counterparts under similar conditions although, the negative impacts of the tropical environment sometimes affect their performance negatively (Ahunu et al, 1993). The overall LWG recorded for the calves in the trials were lower than the range from 295 to 525 g d − 1 average daily gains reported for preweaned calves by Messine et al (2004).…”
Section: Discussionmentioning
confidence: 48%
“…4a to e). Productive characterization of local animals is unknown but it is likely to be similar to results from other countries (Jaitner et al 2004;Jaitner et al 2003;Ahunu et al 1993;de Jode et al 1992;Njie and Agyemang 1991;Tuah and Danso 1985). Similarly to other regions of Guinea Bissau, cattle belong to a specific clan (morança) that owns and manages the animals.…”
Section: Resultsmentioning
confidence: 80%
“…Productive characterization of local animals is unknown as most farmers are illiterate and do not have records. It is however expected to be similar to trypanotolerant cattle found elsewhere in West Africa (Jaitner et al 2003(Jaitner et al , 2004Ahunu et al 1993;de Jode et al 1992;Njie and Agyemang 1991;Tuah and Danso 1985).…”
Section: Cattlementioning
confidence: 91%